2014
DOI: 10.1097/ico.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated (9-mW/cm2) Corneal Collagen Crosslinking for Keratoconus—A 1-Year Follow-up

Abstract: Accelerated corneal CXL is effective in stabilizing topographic parameters after 12 months of follow-up in mild-moderate keratoconus-affected corneas. Improvement in the UDVA and stabilization of all tested corneal parameters were noted after the treatment. However, a longer follow-up with larger cohorts is necessary to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…7 Based on the Bunsen-Roscoe laws of reciprocity, various high-intensity accelerated protocols have emerged to shorten the treatment duration to reduce patient discomfort, while maintaining similar treatment effectiveness as the conventional Dresden protocol. [8][9][10][11][12] Currently, there is still a debate on the effectiveness between conventional CXL and its accelerated counterparts. 13,14 A corneal stromal demarcation line indicating the transition between the anterior cross-linked and posterior untreated corneal stroma could be observed using a slit lamp by as early as 2 weeks after CXL.…”
mentioning
confidence: 99%
“…7 Based on the Bunsen-Roscoe laws of reciprocity, various high-intensity accelerated protocols have emerged to shorten the treatment duration to reduce patient discomfort, while maintaining similar treatment effectiveness as the conventional Dresden protocol. [8][9][10][11][12] Currently, there is still a debate on the effectiveness between conventional CXL and its accelerated counterparts. 13,14 A corneal stromal demarcation line indicating the transition between the anterior cross-linked and posterior untreated corneal stroma could be observed using a slit lamp by as early as 2 weeks after CXL.…”
mentioning
confidence: 99%
“…[30][31][32][33] It seems that the accelerated cross-linking technique will likely be pursued in an effort to stream-line the treatment procedure but more standardized protocols and studies with longer term follow-up are needed.…”
Section: Discussionmentioning
confidence: 98%
“…A retrospective study of 16 eyes treated with riboflavin every 2 minutes for a period of 30 minutes followed by UVA irradiation with 9 mW/cm 2 for 10 minutes found that keratometry measures and visual acuity remained stable in all patients at both 6-month and 12-month follow-up examinations. 32 Other studies using riboflavin for either 10 or 15 minutes followed by UVA irradiation with 30 mW/cm 2 for 3 minutes found that patients had stabilization or improvement in keratometry measures similar to patients treated with the standard epithelial-off cross-linking method (30 min UV light application). 31,33 There was, however, no evidence of improved safety with accelerated cross-linking as there was no difference in endothelial morphology between accelerated versus epithelial-off cross-linking.…”
Section: Epithelial-off Versus Transepithelial Cross-linkingmentioning
confidence: 96%
“…Retrospective cohorts have shown patients with mild to moderate keratoconus undergoing 10 mW/cm 2 treatment for 9 min with improvement in topographic parameters and no complications at 6 month [46] and 1 year [47]. A randomized controlled trial comparing accelerated and conventional CXL showed no difference at 1 year in visual acuity, maximum keratometry, anterior stromal keratocyte density and subbasal nerve density or endothelial cell count [48 & ] (Figs 3 and 4).…”
Section: Accelerated Protocolsmentioning
confidence: 98%